International Accounting and Reporting Issues - 2013 Review - United Nations Conference on Trade; Development (United Nations, 2014)
This volume is dedicated to the topic of human capacity development in relation to meeting the requirements for high-quality corporate reporting. Over the past four years, ISAR has been developing and refining a comprehensive approach to achieving high-quality corporate reporting: the Accounting Development Tool (ADT). The ADT dedicates one of its four pillars to the human capacity for achieving high-quality corporate reporting. There are a number of human capacity related challenges that countries face when implementing corporate reporting standards and codes developed at a global level. It also highlights trends such as the adoption and implementation of international standards and codes, the increasing regional and international cooperation among regulators of the accounting profession, and the emergence of education initiatives.